TEACHING METHODS IN THE MASTERING COURSE “LEGAL REGULATION OF EASEMENT” - Dinsberga, Jolanta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The goal of any university is to train highly qualified specialists who would be competitive on the labour market. Each branch of law or speciality has specific teaching methods designed to bring the desired result, where students are able to acquire knowledge and develop their skills and abilities. The research deals with several teaching methods that could be relevant with respect to the legal framework of easements and presents the results of observations and questionnaire surveys covering students of several bachelor’s degree programmes (Law, Innovation Economics and Business, Accounting and Audit, Interior Design and Culture Management). The research emphasises that even complicated issues may be presented in a simplified and easily understandable manner, thereby promoting the students’ interest in their exercises. It is essential to select the appropriate teaching method and formulate adequate practical exercises.